2002
DOI: 10.1128/jvi.76.3.1400-1414.2002
|View full text |Cite
|
Sign up to set email alerts
|

Oncoviral Bovine Leukemia Virus G4 and Human T-Cell Leukemia Virus Type 1 p13 II Accessory Proteins Interact with Farnesyl Pyrophosphate Synthetase

Abstract: G4 and p13II are accessory proteins encoded by the X region of bovine leukemia virus and human T-cell leukemia virus type 1 (HTLV-1), respectively. Disruption of the G4 and p13 II open reading frames interferes with viral spread in animal model systems, indicating that the corresponding proteins play a key role in viral replication. In addition, G4 is oncogenic in primary cell cultures and is absolutely required for efficient onset of leukemogenesis in sheep. To gain insight into the function of these proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 55 publications
0
65
0
Order By: Relevance
“…Although the significance of these interactions is unclear, it is noteworthy that eukaryotic adenylate kinase, a probable evolutionary descendent of archaeal adenylate kinases, is a mitochondrial protein involved in energy metabolism. A more recent study demonstrated that p13 II also binds to farnesyl pyrophosphate synthetase, an enzyme involved in the mevalonate/squalene pathway, and in the synthesis of farnesyl pyrophosphate, a substrate required for prenylation of Ras (34). This property is shared by G4, a mitochondrially targeted accessory protein expressed by bovine leukemia virus, another complex retrovirus that is classified with HTLV-1 in the Deltaretrovirus genus.…”
Section: Htlv-1 P13 II Function 34431mentioning
confidence: 93%
“…Although the significance of these interactions is unclear, it is noteworthy that eukaryotic adenylate kinase, a probable evolutionary descendent of archaeal adenylate kinases, is a mitochondrial protein involved in energy metabolism. A more recent study demonstrated that p13 II also binds to farnesyl pyrophosphate synthetase, an enzyme involved in the mevalonate/squalene pathway, and in the synthesis of farnesyl pyrophosphate, a substrate required for prenylation of Ras (34). This property is shared by G4, a mitochondrially targeted accessory protein expressed by bovine leukemia virus, another complex retrovirus that is classified with HTLV-1 in the Deltaretrovirus genus.…”
Section: Htlv-1 P13 II Function 34431mentioning
confidence: 93%
“…Consistent with this model, response to FasL and the effects of p13 II are antagonized by a farnesyl transferase inhibitor . These observations are particularly interesting in light of the fact that p13 II was shown to bind to farnesyl pyrophosphate synthase, an enzyme required for the synthesis of isoprenoid precursors necessary for the farnesylation of Ras and other substrates (Lefebvre et al, 2002).…”
Section: Htlv-1 Orf Ii: P13 II and Its Interactions With The Mitochonmentioning
confidence: 99%
“…On the other hand, p13 binds to farnesyl pyrophosphate synthase (FPPS), an enzyme required for the prenylation of Ras (Lefebvre et al, 2002).…”
Section: Rex P12 P13 and P30mentioning
confidence: 99%